Avaliação da aprendizagem dos estudantes do ensino médio de uma escola da Rede Marista e a coerência com os referenciais institucionais - Truda, Viviane Marie Leal (Universidade do Vale do Rio dos Sinos, 2015)
This work has as its theme the learning evaluation of high school students and consistency with the institutional frameworks of the school. In this research, I tried to understand it is conceived and practiced the assessment of student learning, with reference to the Educational Project of the Marist Brazil and the School Rules, from the perspective of directors, pedagogical coordination and educational guidance of a Marist school. In the research, I tried to analyze the concepts of the subject curriculum and evaluation of learning in the management, coordination of pedagogical and educational, and how these actors manage spaces and decision phases of the evaluation of student learning of the studied school. The research was developed from the perspective of a qualitative methodology, and data collection was performed by means of the documents content analysis, accompanied by interviews. We interviewed the subjects that is part of the direction, coordination and pedagogical educational orientation of high school of the studied school. The research was based on Arroyo (2009, 2011, 2012), Cunha (2005), Demo (1997), Freire (1981, 1987, 1993, 2001, 2011, 2014), Hoffman (1992, 2009, 2011), Lück (2007, 2010), Luckesi (2011a, 2011b, 2014a, 2014b), Meurieu (1998, 2002), Sacristan (200), Vygotsky (1991) and others. The Educational Project of the Marist Brazil has emancipatory and liberating theoretical conceptions, and the School Rules are consistent with it. During the search, found detachment in thinking of the subjects in relation to the concepts put in the documents, as well as in relation to assessment practice held at school. From the commitment I made to carry out this study, present a proposal with the objective of deepening and conceptual alignment of structural conceptions of the institution's documents.
Keywords: Avaliação da aprendizagem; Currículo; Estudante; Evaluation of learning; Curriculum; Student; ACCNPQ::Ciências Humanas::Educação